Comprehensive Kinetic Survey of Intestinal, Extra-Intestinal and Systemic Sequelae of Murine Ileitis Following Peroral Low-Dose Toxoplasma gondii Infection - Heimesaat, Markus M.; Dunay, Ildiko R.; Bereswill, Stefan (Frontiers in Cellular and Infection Microbiology, 2019)
We have recently shown that following peroral low-dose Toxoplasma gondii infection susceptible mice develop subacute ileitis within 10 days. Data regarding long-term intestinal and extra-intestinal sequelae of infection are scarce, however. We therefore challenged conventional C57BL/6 mice with one cyst of T. gondii ME49 strain by gavage and performed a comprehensive immunopathological survey 10, 36 and 57 days later. As early as 10 days post-infection, mice were suffering from subacute ileitis as indicated by mild-to-moderate histopathological changes of the ileal mucosa. Furthermore, numbers of apoptotic and proliferating/regenerating epithelial cells as well as of T and B lymphocytes in the mucosa and lamina propria of the ileum were highest at day 10 post-infection, but declined thereafter, and were accompanied by enhanced pro-inflammatory mediator secretion in ileum, colon and mesenteric lymph nodes that was most pronounced during the early phase of infection. In addition, subacute ileitis was accompanied by distinct shifts in the commensal gut microbiota composition in the small intestines. Remarkably, immunopathological sequelae of T. gondii infection were not restricted to the intestines, but could also be observed in extra-intestinal tissues including the liver, kidneys, lungs, heart and strikingly, in systemic compartments that were most prominent at day 10 post-infection. We conclude that the here provided long-term kinetic survey of immunopathological sequalae following peroral low-dose T. gondii infection provides valuable corner stones for a better understanding of the complex interactions within the triangle relationship of (parasitic) pathogens, the host immunity and the commensal gut microbiota during intestinal inflammation. The low-dose T. gondii infection model may be applied as valuable gut inflammation model in future pre-clinical studies in order to test potential treatment options for intestinal inflammatory conditions in humans.